Catalytic and Optical Application of Metal oxide and Carbon Dot Nanostructures: Effect of Morphology and Concentration - Mehta, Akansha (My University, 2018)
The work elaborates the basis of semiconductor photocatalysis with a precise discussion on titanium dioxide TiO2, SiO2 and MnO,2. The introduction section is focused upon the synthesis , band gap tunning, surface modification, sustianable applications of carbon quantam dots (CQDs) and detailed photocatalysis mechanism by semiconductors. Moreover the research gaps, objectives and characterization techniques with specification has also been integrated. The chapter 2 signifies the synthesis of gold nanoparticles dispersed uniformly on mesoporous silica (mAu/SiO2) by homogeneous deposition–precipitation method. Silica provides support and surface area to increase catalytic activity of gold. The Au/SiO2 as photocatalyst was used for the conversion of 4-Nitrophenol (4-NP) to 4- Aminophenol (4-AP). The catalytic conversion was studied by UV-Visible spectroscopy and HPLC quantification method, which shows conversion of nitro group into amino group. The chapter 3 is focused upon the detoxification of harmful dyes through non conventional catalytic processes. This chapter reveals the synthesis of gold-titania (Au/TiO2) mesoporous nanostructure and its photocatalytic performance for degradation of alizarin dye. The chapter 4 gave detailed mechanism for fabrication of solid-phase MnO2 nanoparticles by surfactant template method and were exploited as the photocatalyst for the effective one-step synthesis of amides. The chapter 5 represents a facile method for the fabrication of carbon quantum dots (CQDs) and Au@CQDs, useful for the photocatalytic hydrogen generation from water. The chapter 6 presents some interesting characteristics of CQDs and their fluorescence turn on/off quenching for the detection of 6-Thioguanine (6-TG). The CQDs were fabricated by simple one-step microwave technique and used for the simultaneous reduction of Au3+ to form Au0-CQD core-shell (Au@CQDs) nanocomposites. The chapter 7 illustrates a novel approach based on the methodology to “kill waste by waste”. Firstly the toxic metal like lead (Pb) ions were detected using highly fluorescence carbon quantum dots (CQDs) and after impregnated of TiO2 into the same Pb-CQDs composite, it was further used for the photodegradation of harmful industrial dyes like Reactive brilliant red X-3BS (RBX), Coralene red BS (CRB) and Remazol black XP (CNB). The last chapter 8 signifies the development of novel MnO2@CQD nanocomposite (carbon dots decorated on MnO2 nanorods) which was prepared by a facile one-pot hydrothermal method. These results underline the prospective application of this metal photocatalyst in water treatment.
Keywords: Catalysis; TiO2; MnO,2; Carbon dots